Periaqueductal gray matter modulates the hypercapnic ventilatory response - Lopes, Luana T. [UNESP]; Patrone, Luis G. A. [UNESP]; Bicego, Kenia C. [UNESP]; Coimbra, Norberto C.; Gargaglioni, Luciane H. [UNESP] (Springer, 2012)
The periaqueductal gray (PAG) is a midbrain structure directly involved in the modulation of defensive behaviors. It has direct projections to several central nuclei that are involved in cardiorespiratory control. Although PAG stimulation is known to elicit respiratory responses, the role of the PAG in the CO2-drive to breathe is still unknown. The present study assessed the effect of chemical lesion of the dorsolateral and dorsomedial and ventrolateral/lateral PAG (dlPAG, dmPAG, and vPAG, respectively) on cardiorespiratory and thermal responses to hypercapnia. Ibotenic acid (IBO) or vehicle (PBS, Sham group) was injected into the dlPAG, dmPAG, or vPAG of male Wistar rats. Rats with lesions outside the dlPAG, dmPAG, or vPAG were considered as negative controls (NC). Pulmonary ventilation (Ve), mean arterial pressure (MAP), heart rate (HR), and body temperature (Tb) were measured in unanesthetized rats during normocapnia and hypercapnic exposure (5, 15, 30 min, 7 % CO2). IBO lesioning of the dlPAG/dmPAG caused 31 % and 26.5 % reductions of the respiratory response to CO2 (1,094.3 +/- 115 mL/kg/min) compared with Sham (1,589.5 +/- 88.1 mL/kg/min) and NC groups (1,488.2 +/- 47.7 mL/kg/min), respectively. IBO lesioning of the vPAG caused 26.6 % and 21 % reductions of CO2 hyperpnea (1,215.3 +/- 108.6 mL/kg/min) compared with Sham (1,657.3 +/- 173.9 mL/kg/min) and NC groups (1,537.6 +/- 59.3). Basal Ve, MAP, HR, and Tb were not affected by dlPAG, dmPAG, or vPAG lesioning. The results suggest that dlPAG, dmPAG, and vPAG modulate hypercapnic ventilatory responses in rats but do not affect MAP, HR, or Tb regulation in resting conditions or during hypercapnia.
Keywords: Control of breathing; Hypercapnia; Periaqueductal gray